ASSIS, JOÃO MARCUS FIGUEIREDO; RODRIGUES, DENISE DOS SANTOS. CIDADANIA, MOVIMENTOS SOCIAIS E RELIGIÃO: ABORDAGENS CONTEMPORÂNEAS. RIO DE JANEIRO: EDUERJ, 2013. 252 P. - Gonzaga, Francisco (Debates do NER, 2015)
-